Inattention to Deferred Increases in Tax Bases: How Michigan Home Buyers Are Paying for Assessment Limits - Bradley, Sebastien (The Review of Economics and Statistics, 2017)
Michigan’s implementation of assessment limits gives rise to a wide variation in taxable basis across comparable homes. Exploiting the fact that the resulting differences in property tax liability are temporarily inherited by new homebuyers, I estimate the degree of capitalization of these largely idiosyncratic tax differences to evaluate whether homebuyers understand the tax implications of their home purchases. Consistent with anecdotal evidence but in stark contrast to the traditional view of rational consumer behavior, I find that homebuyers are woefully inattentive to the temporary nature of their initial tax obligations, resulting in an overpayment of nearly $10,000 for the average home.